Ipsilateral foetal-type posterior cerebral artery is associated with cognitive decline after carotid revascularisation - Altinbas, Aysun (BioMed Central, 2014)
BACKGROUND: Stenosis of the internal carotid artery has been associated with cognitive impairment and decline. However, studies testing the effect of carotid revascularisation on cognition have had conflicting results. This may in part be explained by variation in the flow territory of the carotid artery. In 12 to 36% of the patients, the posterior cerebral artery is mainly or exclusively supplied by the internal carotid artery via a foetal-type posterior cerebral artery. In these patients, ipsilateral carotid artery stenosis is likely to result in a larger area with hypoperfusion than in case of a normal posterior cerebral artery. Patients with a foetal-type posterior cerebral artery could therefore benefit more from revascularisation. We compared the effects of carotid revascularisation on cognition between patients with a foetal-type and those with a normal posterior cerebral artery. METHODS: Patients with symptomatic internal carotid artery stenosis ≥ 50%, enrolled in the International Carotid Stenting Study (ICSS) at a single centre, underwent detailed neuropsychological examinations before and 6 months after revascularisation. Cognitive test results were standardized into z-scores, from which a cognitive sumscore was calculated. The primary outcome was the change in cognitive sumscore between baseline and follow-up. Changes in cognitive sumscore were compared between patients with an ipsilateral foetal-type and those with a normal posterior cerebral artery, as assessed with CT or MR angiography. RESULTS: Of 145 patients enrolled in ICSS at the centre during the study period, 98 had both angiography at baseline and neuropsychological examination at baseline and at 6-months follow-up. The cognitive sum score decreased by 0.28 (95% confidence interval, 0.10 to 0.45) in 13 patients with an ipsilateral foetal-type posterior cerebral artery and by 0.07 (95% CI, 0.002 to 0.15) in 85 patients with a normal posterior cerebral artery (mean difference, -0.20; 95% CI, -0.40 to -0.01). This did not change essentially after adjustment for baseline factors. CONCLUSION: An ipsilateral foetal-type posterior cerebral artery appears to increase cognitive decline after carotid revascularisation. Our findings have to be reproduced in an independent study before further implications can be made.